The use of distributed random forest model to quantify risk predictors for tracheostomy requirements in septic patients: A retrospective cohort study. Issue 28 (10th July 2020) - Rodrigues, Lorena Aparecida de Brito; Lago, Alessandra Fabiane; Menegueti, Mayra Gonçalves; Farias, Viviane Aparecida; Auxiliadora-Martins, Maria; Ferez, Marcus Antonio; Martinez, Edson Zangiacomi; Basile-Filho, Anibal
Abstract : Abstract: The search for early clinical risk factors in the intensive care setting may improve the outcome of critically ill patients. The objective of this retrospective study is to identify and quantify early predictors for patients who would require tracheostomy. Five hundred and forty four septic patients were divided in 2 groups: non-tracheostomized (NT) (n = 484) and tracheostomized (T) (n = 60). The patients consisted of 241 males (49.8%) in NT and 27 (45%) in T group, respectively ( P  = .4971). The median and interquartile range difference of age of NT group was of 72 years [59–82] and T of 75 [55.0–83.5] ( P  = .4687). The SAPS 3 for the group NTxT was 70 [55–85] and 85.5 [77–91] ( P  = .0001), the SOFA of 9 [6–13] and 12 [10–14] ( P  = .0002). The comparison of logistic regression analysis for predictors of non-tracheostomy and tracheostomy groups showed an adjusted odds ratio (OR) for SAPS 3 range between 74 and 87 of 18.14 (95%CI = 3.36–97.84) and between 88 and 116 of 27.77 (95%CI = 4.43–174.24) ( P  < .05). For SOFA, the adjusted OR between 10 and 13 was 12.23 (95%CI = 2.46–60.81) and between 14 and 20 was 8.45 (95%CI = 1.58–45.29) ( P  < .05). The need for blood transfusions and dialysis presented an OR of 2.74 (95%CI = 1.23–6.08) and 3.33 (95%CI = 1.43–7.73) ( P  < .05), respectively. Our data shows that SAPS 3 ≥ 74, SOFA ≥ 11, blood transfusions and the need for dialysis were independently associated and could be considered major predictors for tracheostomy requirements in septic patients.